2011
DOI: 10.1111/j.1600-0765.2011.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2X7 purinergic receptor and MEK1/2 in interleukin-8 up-regulation by LL-37 in human gingival fibroblasts

Abstract: These findings indicate that LL-37 induces IL-8 expression via the P2X(7) receptor and the MEK1/2-dependent p44/42 MAP kinases in HGFs, suggesting both direct and indirect involvement of LL-37 in neutrophil recruitment into an inflammatory site within diseased periodontal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 45 publications
(65 reference statements)
4
40
0
2
Order By: Relevance
“…Although LL-37 mediates its responses in most immune cells and endothelial cells via FPR2, it activates CXCR2 in neutrophils, insulin growth factor receptor in gingival fibroblasts, and P2X7 in transfected HEK293 cells (8,(11)(12)(13)(14)47). LL-37 induces chemotaxis, degranulation and chemokine production in mast cells (17-19, 22, 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LL-37 mediates its responses in most immune cells and endothelial cells via FPR2, it activates CXCR2 in neutrophils, insulin growth factor receptor in gingival fibroblasts, and P2X7 in transfected HEK293 cells (8,(11)(12)(13)(14)47). LL-37 induces chemotaxis, degranulation and chemokine production in mast cells (17-19, 22, 23).…”
Section: Discussionmentioning
confidence: 99%
“…Most effects of LL-37 appear to be mediated via the activation of G protein-coupled formyl peptide receptor 2 (FPR2; earlier known as FPRL1) on monocytes, T cells, and endothelial cells (3, 8 -11). LL-37 also activates chemokine receptor CXCR2 in human neutrophils (12), purinergic receptor P2X7 in fibroblasts (13), and insulin growth factor receptors in epithelial cells (14).…”
mentioning
confidence: 99%
“…HGFs were then trypsinized, and their number was expanded for subsequent experiments. For cell treatment, HGFs were starved from FBS for 6 h prior to treatment with non-toxic doses of LL-37, as previously reported [21], or 1 ng/ml of IL-1β in the presence or absence of pharmacological inhibitors for specific times, since it has previously been shown that FBS can induce COX-2 expression and PGE 2 production [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Stimulation of the P2X 7 R in gingival fibroblasts was also implicated in the up-regulation of IL-8 by the antimicrobial peptide LL-37 (Montreekachon et al, 2011). LL-37 can attract leukocytes and up-regulate immune-related genes in various cell types (Zanetti, 2004), and levels of LL-37 are perturbed in periodontitis (Puklo et al, 2008).…”
Section: Atp and Gingival Cellsmentioning
confidence: 99%